Effect of Positive Devience Approach to Parenting in Malnutrition Children in Muke Village - East Nusa Tenggara - Indonesia - Tat, Florentianus; Herwanti, Elisabeth; ., Wanti; ., Kusmiyati; Ekawati, Christine JK (International Journal of Innovative Research in Medical Science, 2019)
The percentage of malnutrition and stunting are still a major problem in east Nusa Tenggara Indonesia. Therefore we need a way to overcome these nutritional problems, among others, with the Positive Deviance Approach. This method is an act of community empowerment by transferring positive behaviour in mothers with malnutrition children. The research objective is Identify the effect of a positive deviance approach on mothers who have malnourished children. Subject and Method: this research is pre-experimental with one group pre-post test design. Data collection on 31 mothers who have malnutrition children. Result: after the intervention the mother's knowledge increases regarding feeding, child care and environmental health. After intervention maternal behavior increased regarding feeding, child care and environmental health. Statistical analysis shows that there is a significant influence between a positive deviance approach to experience with mothers' knowledge (p=0,03) and behavior (p=0,04) about feeding, caring for children and environmental health. Conclusion: The Positive Deviance approach gives an effect on increasing the knowledge and behavior of mothers in feeding, child care and environmental health. Recommendation: Use the Positive deviance method for changing people's behavior.